A concepção de linguagem de professoras alfabetizadoras e sua influência no ensino do ato de ler - Correa, Joelma Reis; Arena, Dagoberto Buim [UNESP] (My University, 2012)
This article aims to analyze literacy teachers’ conception of language from the classroom scenes that demonstrate the teaching of the act of reading. For the realization of the objective was carried out research in education like ethnography with two teachers in the 2nd year of elementary school a school of the Municipal located in the city of Sao Luis in Maranhão State, whose main instrument for data generation was participant observation. Also, I was guided by microgenetic analysis in order to focus our gaze to the particular aspect of the situation with attention to the “clues” to extract meaningful data. Authors such as Mikhail Bakhtin (1995, 2003) and scholars in the fi eld of reading, Josette Jolibert (1994), Elie Bajard (2007), among others, were considered core to grasp the meaning assigned by the subjects to teaching the act of reading. The fi ndings reveal that the design language of the teacher infl uences the direction of your practice, determining how to teach reading.

Este Artigo tem por objetivo analisar a concepção de linguagem de professoras alfabetizadoras, a partir de cenas de sala de aula que demonstram o ensino do ato de ler. Para a efetivação do objetivo proposto foi realizada uma pesquisa em educação do tipo etnográfi ca com duas professoras do 2º ano do Ensino Fundamental de uma escola da Rede Municipal localizada na cidade de São Luís no Estado do Maranhão, cujo principal instrumento de geração de dados foi a observação participante. Além disso, me orientei pela análise microgenética com o objetivo de centrar o olhar para o aspecto particular da situação com atenção às “pistas” signifi cativas para extrair dados. Autores como Mikhail Bakhtin (1995, 2003) e estudiosos da área da leitura, Josette Jolibert (1994), Élie Bajard (2007), dentre outros, foram considerados nucleares para apreender o signifi cado atribuído pelos sujeitos ao ensino do ato de ler. As conclusões revelam que a concepção de linguagem do professor infl ui no direcionamento da sua prática, determinando o modo de ensinar a ler.
Keywords: alfabetização; leitura